Students Anxiety in Learning Speaking - Mahmuda, Teuku Imam (Universitas Serambi Mekkah, 2023)
This research was conducted to investigate the types of students' anxiety in speaking English and the factors that cause language anxiety in speaking English. This study uses a qualitative method. Participants in this research were 32 second grade students from SMP Negeri 1 Darul Imarah. Data obtained from questionnaires. The results showed that there are three types of anxiety felt by students when speaking English, namely state anxiety, trait anxiety, and situational anxiety. In addition, factors that cause students' anxiety when speaking English are fear of speaking inaccurately, fear of negative evaluation, and low speaking skills.